The Narrative of Artivism as a Trend in Advertising: Campaign: “In Spain we call it equality” - Sánchez Serrano, Diana; Ortega Fernández, Eglée; Toledano Cuervas-Mons, Fernando (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2022)
The democratization of communications through social media has promoted a change in the consumer profile. It is perceived that society shows a more open awareness, focused on sustainability, care for the environment and social inclusion. Artivism, understood as a phenomenon that removes art from museums and galleries to give it a social function, could be an opportunity for a change of model where the emotions that art and activism arouse come together to achieve a narrative with a greater effect on the audience to whom the advertising seeks to reach.